Impact of Project-Based Learning on Mathematical Communication and Critical Thinking Skills in Grade VII Statistics Learning - Rizka Tri Andini; Fibri Rakhmawati (MASI Mandiri Edukasi, 2025)
This study addresses the challenge of low levels of mathematical communication and critical thinking among students, often stemming from the widespread use of traditional, teacher-centred instructional methods. The objective of this research is to examine the impact of the Project-Based Learning (PjBL) model on seventh-grade students' mathematical communication and critical thinking skills in statistics. A quasi-experimental design with a Nonequivalent Control Group was applied. Participants included 35 students in the experimental group (Class VII-3, using PjBL) and 35 students in the control group (Class VII-5, using conventional methods) at MTs Al-Jam'iyatul Washliyah Tembung. Data was collected using tests for critical thinking and observation sheets for mathematical communication skills. The results showed significantly higher average scores in the experimental group compared to the control group for both skills. Specifically, the mean scores for mathematical communication were 88.05 (experimental) versus 48.84 (control), and for critical thinking were 74 (experimental) versus 50.28 (control). The Independent-Samples t-Test confirmed significant differences (Sig. 2-tailed = 0.000 < 0.05) for both skills, while ANOVA (F = 43.634, Sig. = 0.000 < 0.05) further confirmed PjBL's significant positive effect on learning outcomes. These findings demonstrate that the Project-Based Learning (PjBL) model is effective in enhancing students' mathematical communication and critical thinking skills.